KONTRIBUSI PT UNILEVER SEBAGAI PERUSAHAAN MULTINASIONAL DALAM MENGATASI SAMPAH PLASTIK DI INDONESIA DENGAN MELALUI BANK SAMPAH - Novies Nugraeni (2022)
Globalization has given rise to new actors in the international world, namely Multinational Corporations. Indonesia as a developing country is also affected by globalization, namely the entry of multinational companies (MNCs) in Indonesia. With the entry of multinational companies in Indonesia, they have made a positive impact on development in Indonesia by direct investment or technology transfer. PT. Unilever Indonesia, Tbk is a multinational company that has been operating in Indonesia. PT. Unilever Indonesia, Tbk is a multinational company that has been operating in Indonesia. PT. Unilever Indonesia, Tbk is one of the MNCs guided by sustainable business. To improve its image, PT. Unilever Indonesia complies with the laws and regulations regarding Corporate Social Responsibility (CSR). PT. Unilever Indonesia, Tbk is committed to implementing CSR practices in Indonesia by establishing the Unilever Indonesia Foundation. In the practice of CSR in Indonesia, Unilever contributes to managing waste in Indonesia, where Indonesia has challenges in sustainable development, namely the problem of plastic waste. This study aims to determine the contribution made by PT. Unilever Indonesia, Tbk on the management of plastic waste in Indonesia. The approach used in this research is descriptive qualitative with data collection and data analysis methods. Primary data obtained by interview and secondary data obtained from literature and other sources as data collection. Theories and concepts as a research framework use the concept of Sustainable Development, Multinational Corporations, and the Concept of Corporate Social Responsibility. The results of this study will explain that PT. Unilever Indonesia, Tbk carries out CSR practices in Indonesia by contributing to managing plastic waste in Indonesia through the Waste Bank.